Labour at the Lakehead ethnicity, socialism, and politics, 1900-35 - Beaulieu, Michel S. (UBC Press, 2011)
In the early twentieth century, the Canadian Lakehead was known as a breeding ground for revolution, a place where harsh conditions in dockyards, lumber mills, and railway yards drove immigrants into radical labour politics. This intensely engaging history reasserts Northwestern Ontario's rightful reputation as a birthplace of leftism in Canada by exposing the conditions that gave rise to an array of left-wing organizations, including the Communist Party, the One Big Union, and the Industrial Workers of the World. Yet, as Michel Beaulieu shows, the circumstances and actions of Lakehead labour, especially those related to ideology, ethnicity, and personality were complex; they simultaneously empowered and fettered workers in their struggles against the shackles of capitalism. Cultural ties helped bring left-wing ideas to Canada but, as each group developed a distinctive vocabulary of socialism, Anglo-Celtic workers defended their privileges against Finns, Ukrainians, and Italians. At the Lakehead, ethnic difference often outweighed class solidarity -- at the cost of a stronger labour movement for Canada.